Health, body condition and blood metabolites in reindeer after submaintenance feed intake and subsequent feeding - Nilsson, A.; Danell, Ö.; Murphy, M.; Olsson, K.; Åhman, B. (Rangifer, 2000)
The transition from experimentally induced poor nutritional conditions to feeding was studied with 69 eight-month-old female reindeer (Rangifer tarandus tarandus). During a pre-experimental period, all reindeer were fed a simulated winter diet with 80% lichens Cladina spp. and 20% Vaccinum myrtillus shrubs and Salix spp. leaves (lichen diet) ad lib. The reindeer were divided into five groups. A control group (group C) was fed the lichen diet ad lib. throughout the experiment. Four groups were fed half of that ration for eight days and were then totally deprived of feed for one day (restriction period). During the following 34 days (feeding period) the groups were re-fed the lichen diet (group L), fed pelleted reindeer feed combined with either lichen (group PL) or grass silage (group PS), or fed silage with a gradually increasing addition of pellets (group SP). Weekly measurements of blood samples and body weighr showed that the control group remained clinically healthy and had stable blood plasma concentrations of protein, urea, glucose and insulin throughout the experiment, but they lost weight. At slaughter, before and after the restriction period, all animals had lost rumen-free body weight, but the reindeer fed a restricted amount of feed lost more than the control group. Also the plasma metabolites were affected by the restricted feeding, with increased concentrations of urea and decreased concentrations of glucose. Group L responded immediately to the ad lib. feeding with blood metabolite levels rapidly approaching those of group C. The body weight developments were similar in groups L and C. Although the feed rations were increased gradually, diarrhoea occurred in some animals belonging to groups PL and PS within the first week of the feeding period. All reindeer recovered, after antibiotic treatment of the worst affected animals. The PL and PS groups, which had high contents of metabolisable energy and crude protein in their diets, showed increased con-centtations of plasma protein, urea and insulin. At the end of the feeding period, these groups had increased their body and carcass weights and gained fat, whereas reindeer fed the lichen diet had lost weight. Severe health problems (malnutrition and so-called wet belly) occurred in group SP during the first weeks of feeding and led to loss of animals, and consequently the SP group was excluded from the remainder of rhe experiment. The general conclusion is that the lichen diet did not cause any digestive problems, but resulted in a continuous decline in body weight and small or deficient fat reserves. After the initial diarrhoea, feeding with diets comprising pellets from the start resulted in improved condition, expressed as increased body weight, fat gain and higher concentrations of plasma protein, urea and insulin in relation to the control group. The diet initially based on grass in the form of silage of the given quality seemed insufficient as feed to reindeer calves in a poor nutritional state.